الصراع بين الشرق والغرب في رواية موسم الهجرة إلى الشمال لطيب صالح أنموذجا - علي شريف, شيماء (كلية الأدب العربي والفنون, 2025)
تعدّ رواية موسم الهجرة إلى الشّمال لطيب صالح من أبرز الرّوايات العربية التي عالجت موضوع الصّراع الحضاري بين الشّرق والغرب من خلال شخصية مصطفى سعيد، حيث قدّم لنا صورة معقدة لهذا الصّراع حيث يتداخل فيه الجانب الشّخصي بالبعد الحضاري والسّياسي، مصطفى سعيد هو ابن بيئة شرقية تقليدية إلّا أنّ رحلته إلى الغرب كشفت له عالما مختلفا من القيم والثّقافات، مما جعله يعيش أزمة هوية عميقة. تجسد الصّراع أوّلا في إحساس مصطفى سعيد بالانبهار إزاء الحضارة الغربية ثم في محاولته السيطرة على هذا العالم الجديد عن طريق التّفوق العلمي واستغلال علاقاته العاطفية كنوع من الانتقام الرّمزي للاستعمار الغربي ومع ذلك فإنّ هذه المحاولات باءت بالفشل ممّا يعمق شعوره بالاغتراب والضّياع، في النّهاية تبرز الرّواية أن الهجرة لم تكن حلا بل كانت بداية لصراع داخلي طويل مما يجعل الهجرة إلى الشّمال رمز من لضياع الهوية أمام ثقافتين متضادتين. Season of Migration to the North by "Tayeb Salih" is one of the most prominent Arabic novels that dealt with the subject of the civilizational conflict between East and West through the character of Mustafa Saeed, as he presented us with a complex picture of this conflict in which the personal aspect is intertwined with the civilization and political dimension. Mustafa Saeed is the son of a traditional Eastern environment, but his journey to the West revealed to him a different world of values ​​and cultures, which made him experience a deep identity crisis. The conflict is embodied first in Mustafa Saeed's sense of fascination with Western civilization, then in his attempt to control this new world through scientific superiority and exploiting his emotional relationships as a kind of symbolic revenge against Western colonialism. However, these attempts fail, which deepens his feeling of alienation and loss , In the end, the novel highlights that migration was not a solution, but rather the beginning of a long internal conflict, making migration to the north a symbol of the loss of identity in the face of two opposing cultures.
Keywords: الصّراع، الغرب، الشّرق، مصطفى سعيد، الطّيب صالح، الهجرة.; Conflict, West, East, Mustafa Saeed, Tayeb Salih, Migration